At home with the empire metropolitan culture and the imperial world - Hall, Catherine 1946-; Rose, Sonya O. (Cambridge University Press, 2006)
This pioneering 2006 volume addresses the question of how Britain's empire was lived through everyday practices - in church and chapel, by readers at home, as embodied in sexualities or forms of citizenship, as narrated in histories - from the eighteenth century to the present. Leading historians explore the imperial experience and legacy for those located, physically or imaginatively, 'at home,' from the impact of empire on constructions of womanhood, masculinity and class to its influence in shaping literature, sexuality, visual culture, consumption and history-writing. They assess how people thought imperially, not in the sense of political affiliations for or against empire, but simply assuming it was there, part of the given world that had made them who they were. They also show how empire became a contentious focus of attention at certain moments and in particular ways. This will be essential reading for scholars and students of modern Britain and its empire